Strategi Guru dalam Menangani Gangguan Keterlambatan Berbicara (Speech Delay) yang Berpengaruh Terhadap Interaksi Sosial Anak Usia Dini di TK Negeri Pembina Surabaya - Taseman Taseman; Safaruddin Safaruddin; Nasrul Fuad Erfansyah; Wilujeng Asih Purwani; Fahriza Femenia Femenia (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2020)
The purpose of this research is to find out the teacher's strategy in dealing with delays in speaking disorders that affect the social interaction of early childhood. The research population is Surabaya State Kindergarten Students. This type of research is the field using data collection techniques such as observation, interviews. The results showed that the specific speech delay experienced by children in TK Negeri Pembina Surabaya was due to two factors, namely internal in children originating from parents' innate factors, and external factors due to lack of language stimulation from their parents. Although children experience delays in speaking, but the situation of children in TK Negeri Pembina Surabaya can still develop better and finally be able to follow the development of the language of other friends through a good teacher strategy as well.